2007
DOI: 10.1093/brain/awm212
|View full text |Cite
|
Sign up to set email alerts
|

Refining genotype phenotype correlations in muscular dystrophies with defective glycosylation of dystroglycan

Abstract: Muscular dystrophies with reduced glycosylation of alpha-dystroglycan (alpha-DG), commonly referred to as dystroglycanopathies, are a heterogeneous group of autosomal recessive conditions which include a wide spectrum of clinical severity. Reported phenotypes range from severe congenital onset Walker-Warburg syndrome (WWS) with severe structural brain and eye involvement, to relatively mild adult onset limb girdle muscular dystrophy (LGMD). Specific clinical syndromes were originally described in association w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
357
0
9

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 389 publications
(388 citation statements)
references
References 33 publications
12
357
0
9
Order By: Relevance
“…8 With regard to cardiac findings in patients with mutations in the POMT2 gene, a study of nine patients found one to have right bundle branch block. 6 In a second study of four patients, one patient had left ventricular hypertrophy at the age of 3.5 years. 1 The enlargement of the aortic root is usually asymptomatic and is often found incidentally in the course of imaging studies.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…8 With regard to cardiac findings in patients with mutations in the POMT2 gene, a study of nine patients found one to have right bundle branch block. 6 In a second study of four patients, one patient had left ventricular hypertrophy at the age of 3.5 years. 1 The enlargement of the aortic root is usually asymptomatic and is often found incidentally in the course of imaging studies.…”
Section: Discussionmentioning
confidence: 95%
“…Fukutin, fukutinrelated protein (FKRP) and LARGE may be involved in glycosylation, but their exact functions remain unknown. 6 The DPM3 gene, encoding a subunit of DOL-P-Man synthase, was recently associated with CMD in a patient with muscular dystrophy and reduced a-dystroglycan staining but without intellectual disabilities. 9 Finally, mutations in DAG1 encoding a-dystroglycan were identified in a patient with a form of limb girdle muscular dystrophy who had normal brain imaging and relatively mild muscular involvement but intellectual disabilities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, many patients with dystroglycanopathy still remain genetically unidentified. 5 Stevens et al 6 recently reported that mutations in the gene b-1,3-N-acetylgalactosaminyltransferase 2 (B3GALNT2; MIM 610194) cause congenital muscular dystrophy and hypoglycosylation of a-dystroglycan with, in most cases, severe brain involvement.…”
Section: Introductionmentioning
confidence: 99%